PENDAPAT PESERTA DIDIK TENTANG MANFAAT LAYANAN BIMBINGAN KELOMPOK DALAM PENYESUAIAN DIRI DI SEKOLAH ( Studi di SMA Negeri 2 Pancung Soal) - Lanofita, Roza; Helma, Helma; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
The purpose of this research is to express studentsâs opinion on the benefits of counseling services in the adjustment group at SMA N 2 pancung soal. Type of research is descriptive. The research was conducted in SMA N 2 pancung soal. With a total sample of 98 peoples. The instrument used in this study was a questionnaire. The research results revealed that: (1) the studentsâs opinion about benefits of group counseling services after adjustment by a percentage of 56.01% of teachers in the category of less agree, (2) the studentsâs opinion about benefits of group counseling services in conformity with friends peer in the category of less agree. Based on the research findings with a percentage of 52.47%, it is suggested to the supervising teacher to provide tutoring services to students of the faction adjustment increase learners in learning with the teacher. For parents, in order to provide care and guidance to the children in his adjustment in improving learning. For principals shauld be able to pay attention to the implementation of group counseling services in an effort to improve studentsâs adjustment in advanced learning and for researchers to examine other factors associated with the adjustment of students with teachers and peers.